Exploring the impact of social influence and halal certification on repurchase intention: The mediating role of trust in online purchases of imported halal food in Indonesia - Syaefulloh, Syaefulloh; Alfansi, Lizar; Hadi, Effed Darta; Salim, Muhartini (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the influence of Social Influence and Halal Certification on Repurchase Intention, with Trust as a moderating variable in the online purchase of imported halal food in Indonesia. Methods: The sample consisted of 260 consumers who made online purchases of imported halal food in Indonesia. Data collection was conducted via a Google Form survey distributed online to respondents. Partial Least Square Structural Equation Modeling (PLS-SEM) was used to test the research hypotheses. Results: The results indicate that Performance Expectancy (PE) significantly positively influences trust (TR). Social Influence (SI) significantly impacts Trust (TR), strongly shaping consumer confidence. Halal Certification plays a significant role in enhancing consumer trust regarding online purchases of imported halal food. Consumer Trust (TR) significantly affects Repurchase Intention (RI). SI also significantly influenced RI. Although Halal Certification (HC) boosts consumer trust in product quality, its effect on RI is not significant. SI significantly impacts RI through the mediation of trust. HC significantly influenced RI, which was fully mediated by trust. Conclusions: Social Influence and Halal Certification both enhance consumer Trust, which significantly drives Repurchase Intention, with Trust fully mediating the effect of Halal Certification and partially mediating the effect of Social Influence, while Halal Certification alone does not directly influence repurchase behavior. Limitations: This study has limitations regarding the sample, which only includes consumers from urban areas, necessitating caution in generalizing the findings to rural populations. Additionally, cultural factors and religiosity impacting trust were not included as control variables. Contribution: This study provides practical insights for e-commerce businesses and halal food importers regarding the importance of halal certification and social influence in shaping consumer trust and repurchase intention. Furthermore, it enriches the literature on Muslim consumer behavior in the digital context. Novelty: This research contributes new insights by examining the role of trust as a moderating variable in online purchases of imported halal food, a relatively under-researched area, particularly in Indonesia, the country with the largest Muslim population in the world.